2007
DOI: 10.1366/000370207782217725
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Analysis of a Continuous-Flow Ozonolysis Reaction Using Raman Spectroscopy

Abstract: We describe the use of an on-line Raman analyzer to quantitatively track the levels of trans-stilbene, benzaldehyde, and alpha-methoxybenzyl hydroperoxide in a continuous flow ozonolysis reactor. Quantitative analysis is carried out using spectral stripping in order to overcome baseline artifacts inherent in simple peak area determinations and to incorporate prior knowledge into the analytical model. The performance of spectral stripping is compared to partial least squares (PLS) analysis. The effect of two pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The use of IR helps marry the rate of ozonolysis production with reaction rate and amount of the alkene present as it is introduced in a stream (306). Raman has also been used to monitor the reaction (307).…”
Section: Ozonolysismentioning
confidence: 99%
“…The use of IR helps marry the rate of ozonolysis production with reaction rate and amount of the alkene present as it is introduced in a stream (306). Raman has also been used to monitor the reaction (307).…”
Section: Ozonolysismentioning
confidence: 99%
“…Several pharmaceuticals are manufactured using an ozonolysis step, which can be readily tracked with Raman spectroscopy [184] . Pelletier et al demonstrated continuous quantitative concentration measurement of trans -stilbene reacting to give benzaldehyde and α -methoxybenzyl hydroperoxide, a model reaction [184] .…”
Section: Ozonolysismentioning
confidence: 99%
“…A computational approach introduced in this work for the removal of light scattering is based on automated interference subtraction methods often used in the spectral domain [ 20 , 21 ]. These methods adjust the amount of an interfering profile until the first- or second-derivative of the spectral profile is at a minimum (i.e.…”
Section: Introductionmentioning
confidence: 99%